KEMAMPUAN SISWA MENGANALISIS TEKS ANEKDOT DENGAN METODE PICTURE AND PICTURE ( MEDIA GAMBAR ) SMK SWASTA NURUL AMALIYAH TANJUNG MORAWA - Sri Rahayu, Lisa Septia Br Ginting (EDUCATE, 2025)
On social media, images have a significant influence on society. Therefore, students should analyze images carefully to avoid influencing opinions. Therefore, the author felt the need to conduct research on: Students' Ability to Analyze Anecdotal Texts Using the Picture and Picture Method (image media) in Grade X Students of Nurul Amaliyah Private Vocational High School, Tanjung Morawa, in the 2020-2021 Academic Year. The population in this study was all 102 Grade X students of Nurul Amaliyah Private Vocational High School, Tanjung Morawa, in the 2020-2021 Academic Year, consisting of three classes. From this population, a random sample of 30 students was selected. The research tools used for data collection were questionnaires and essay tests. The tests were used to determine students' ability to analyze anecdotal texts. To determine the students' average score, the author used the data processing technique of using the mean formula, determining the standard deviation, and then calculating the final score. The study found that the picture and picture learning model significantly influenced or impacted students' ability to analyze anecdotal texts in grade 10 students at Nurul Amaliyah Private Vocational School, Tanjung Morawa, in the 2020-2021 academic year.